1983
DOI: 10.1038/hdy.1983.69
|View full text |Cite
|
Sign up to set email alerts
|

On the polymorphism of cyanogenesis in Lotus corniculatus L. IX. Selective herbivory in natural populations at Porthdafarch, Anglesey

Abstract: SUMMARYThe L. corniculatus populations at Porthdafarch are polymorphic for the characters of leaf cyanogenesis, petal cyanogenesis and keel petal colour. Plants with cyanogenic leaves and petals occur less frequently on the sea cliffs than inland and previous studies have obtained circumstantial evidence of a link between the dine in leaf cyanogenesis and the distribution of selectively grazing molluscs.Counts of leaf and petal damage have confirmed that plants on the cliffs are grazed less heavily than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This hypothesis is contingent on there being less floral herbivory on cyanogenic plants relative to acyanogenic plants, which is reasonable given observations from other plants with cyanogenesis polymorphisms (e.g., Lotus corniculatus ; Compton et al. ). Future studies are needed to determine whether floral and foliar herbivory are correlated in T. repens .…”
Section: Discussionmentioning
confidence: 63%
“…This hypothesis is contingent on there being less floral herbivory on cyanogenic plants relative to acyanogenic plants, which is reasonable given observations from other plants with cyanogenesis polymorphisms (e.g., Lotus corniculatus ; Compton et al. ). Future studies are needed to determine whether floral and foliar herbivory are correlated in T. repens .…”
Section: Discussionmentioning
confidence: 63%
“…This is in contrast to the polymorphism of leaf cyanogenesis in L. corniculatus where approximately 25 per cent of the recorded populations are monomorphic (Jones, 1977 (Compton et a!., 1983b), where the dark morph increased in frequency from 54 per cent (June 1979) to 20 per cent (May 1982) in one group of plants and from 107 per cent (June 1979) to 129 per cent (May 1982) in a closely adjacent group of plants. On both occasions the damage to the flowers was recorded, but no evidence of differential herbivory was obtained.…”
Section: Analysis Of Variance After Relevant Transformationsmentioning
confidence: 52%
“…This has been demonstrated in white clover where cyanogenic populations had less leaf damage by insects and better seedling survival than acyanogenic populations (Pederson and Brink, 1998). Several other field and laboratory studies on BFT and white clover have also demonstrated that cyanogenic plants were less preferred by several insect species and mollusks than acyanogenic plants (Compton et al, 1983; Compton and Jones, 1985; Hughes, 1991; Ellsbury et al, 1992). In adult plants, leaf loss may not be as critical as it is in seedlings because adult plants can easily compensate for lost leaves (Crawford‐Sidebothum, 1972).…”
Section: Resultsmentioning
confidence: 88%